2017
DOI: 10.3389/fpsyg.2017.01095
|View full text |Cite
|
Sign up to set email alerts
|

Production and Comprehension of Pantomimes Used to Depict Objects

Abstract: Pantomime, gesture in absence of speech, has no conventional meaning. Nevertheless, individuals seem to be able to produce pantomimes and derive meaning from pantomimes. A number of studies has addressed the use of co-speech gesture, but little is known on pantomime. Therefore, the question of how people construct and understand pantomimes arises in gesture research. To determine how people use pantomimes, we asked participants to depict a set of objects using pantomimes only. We annotated what representation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 73 publications
(122 reference statements)
3
53
0
Order By: Relevance
“…At first exposure, they recruit a powerful gestural system that may or may not match the form and meaning of newly encountered signs. These results are in line with more general findings showing that new knowledge is evaluated first in the context of already existing schemas (van Kesteren, Rijpkema, Ruiter, Morris, & Fernández, 2014). These existing schemas are updated after learning, when the acquired signs develop more robust lexical representations and participants distance themselves from their gestures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…At first exposure, they recruit a powerful gestural system that may or may not match the form and meaning of newly encountered signs. These results are in line with more general findings showing that new knowledge is evaluated first in the context of already existing schemas (van Kesteren, Rijpkema, Ruiter, Morris, & Fernández, 2014). These existing schemas are updated after learning, when the acquired signs develop more robust lexical representations and participants distance themselves from their gestures.…”
Section: Discussionsupporting
confidence: 90%
“…In line with these findings, we hypothesized that if signs with high overlap with gesture are processed more easily compared to signs with low overlap with gesture, reduced amplitude of the N400 component should be observed for the high-overlap condition compared to the low-overlap condition. Second, earlier work has linked N400 amplitude to semantic integration (e.g., van Berkum, Hagoort, & Brown, 1999). It might be easier to integrate an observed high overlap sign (vs. a low overlap sign) with the corresponding preceding word in our paradigm, because of the availability of a gestural schema for the signs with high overlap with gesture.…”
mentioning
confidence: 92%
“…Within the manual modality, evidence has shown that people reliably fall back on specific modes of representation when they are asked to express objects in silent gesture. A study showed that after researchers asked a group of adults to represent only with their hands 60 pictures of objects from the Boston Naming Task (Roomer, Hoogerwerf, & Linn, 2011), most concepts were expressed using a default mode of representation that most of the time involved the acting strategy (van Nispen et al, 2014;van Nispen et al, 2017). Interestingly, the concepts depicted through default strategies were also guessed better by a different group of participants (van Nispen et al, 2017).…”
Section: Silent Gesture: a Window Onto Systematic Visible Representatmentioning
confidence: 99%
“…The roundness of a ball, the way to operate a saw, the shape of a pyramid-these are all physical sensorimotor attributes that can be grounded in the body for communicative purposes. Individuals build analogical relationships between a real object and a manual form by mapping specific features of their conceptual representations onto an iconic gestural structure (Calbris, 2011;Cooperrider & Goldin-Meadow, 2017;Taub, 2001;van Nispen, van de Sandt-Koenderman, & Krahmer, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation